Formulasi Krim Ekstrak Etanol Daun Kirinyuh (Euphatorium odoratum. L) untuk Penyembuhan Luka - Yenti, Revi; Afrianti, Ria; Afriani, Linda (Majalah Kesehatan Pharmamedika, 2011)
Formulation of cream for wound healing has been studied. Cream formula consisting of 2.5%, 5% and 10% ethanolic extract of kirinyuh leaf (Euphatorium odoratum L.) as an active ingredient. The formulas were evaluated for their organoleptic, homogeneity, cream type, pH, washability, stability of temperature, particle size distribution, skin irritation, and effect wound healing in mice white male with Morton's method. The evaluation formulation results showed physicaly stable and provide a healing effect on wound. The results showed that the formula cream with a concentration of 10% at 12th day, with 100% percentage of wound healing.